Tuber initiation, duration of the vegetative cycle and heat tolerance in potato genotypes - Lyra, Danilo Hottis; Ribeiro, Guilherme Henrique Martins Rodrigues; Figueiredo, Izabel Cristina Rodrigues de; Guedes, Marcio Lisboa; Carneiro, Otávio Luiz Gomes; Pinto, César Augusto Brasil Pereira; Pereira, Arione da Silva (Pesquisa Agropecuaria Brasileira, 2015)
The objective of this work was to determine the relationship of the time for tuber initiation and of the duration of the vegetative cycle with heat tolerance in potato. Clone groups with different tuber initiation times and duration of the vegetative cycle were defined and evaluated in two environments, and their morphophysiological indices were determined under heat stress conditions. The amplitude for the beginning of tuberization was 31.8 days, and for the duration of vegetative cycle was 30.3 days. The formed groups of clones showed the following parameters: early tuberization and short cycle, early tuberization and long cycle (PL), late tuberization and short cycle, and late tuberization and long cycle. Under heat stress conditions, the production of large tubers of the PL group was higher than that of the other groups. Six clones (IRF 10‑24, IRF 7‑61, IRF 2‑71, IRF 2‑14, IRF 6‑104, and IRF 10‑44) and three checks ('Markies', CBM 16‑16, and CBM 9‑10) were considered tolerant to heat stress (21.2ºC daily average), and responded favorably to environment at mild temperatures (19.0ºC daily average). Dry matter partitioning to the tubers was faster in the PL clone group. Clones of early tuberization and long vegetative cycle showed higher tolerance to heat stress, with higher tuber production than the other groups.